Analysis of Learning Interest of Elementary School Students in Mathematics Learning - Deninda Rezky Ramadhani; Rasidi; Sukma Wijayanto (Urecol Journal. Part H: Social, Art, and Humanities, 2022)
This study aims to determine students' interest in learning mathematics. This research was conducted at SD Negeri Trasan 2, Bandongan sub-district, Magelang Regency. This research was conducted using data collection methods in the form of interviews with teachers, students and parents, observations on teachers, students, and parents, as well as observing several supporting documents. This study used a qualitative approach with a qualitative descriptive type. Test the validity of the data using triangulation techniques. The triangulation used, source triangulation and technique triangulation. The data analysis technique uses data analysis techniques from Miles and Huberman which consists of 4 stages, namely, data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that students' interest in learning in mathematics subjects is that students feel happy and have ownership with mathematics because the teacher in delivering teaching materials uses interesting media. Teachers also have learning support facilities in the form of a fairly complete learning administration such as PROTA, PROMES, syllabus, lesson plans, modules, worksheets, daily journals, etc. However, in practice they are often faced with various obstacles including students who often do not focus on the subject matter, students who are passive in discussion activities.